Promelaxin Microenemas Are Non-inferior to Oral Polyethylene Glycol for the Treatment of Functional Constipation in Young Children: A Randomized Clinical Trial - Caterina Strisciuglio; Vincenzo Coppola; Marina Russo; Carlo Tolone; Gian Luigi Marseglia; Alberto Verrotti; Silvia Caimmi; Claudia Caloisi; Valeria D'Argenio; Valeria D'Argenio; Lucia Sacchetti; Annamaria Staiano (Frontiers Media S.A., 2021)
Background: Polyethylene glycol (PEG) is recommended as first-line treatment of pediatric functional constipation. However, the oral route of administration is often poorly feasible in children mostly due to poor palatability. Promelaxin microenemas exert a topical evacuative action and may offer a valuable option in pediatric FC.Aim: To assess whether Promelaxin microenemas would be non-inferior to PEG 4000 in young children with FC.Methods: This is a randomized, open-label, multi-centric, non-inferiority trial enrolling infants and young children aged 6-48 months, with FC according to Rome III criteria. After 1 week of run in, children were randomized to 2 weeks of Promelaxin or PEG, followed by a 6-week on-demand treatment period. Primary endpoint was response rate to randomized treatment, with "response" defined as at least 3 evacuations per week and an average increase of at least one evacuation per week as compared to baseline. Safety, stool consistency and the analysis of fecal microbiota were secondary endpoints.Results: Out of the 158 patients who entered the trial, 153 patients were treated (77 and 76, PEG and Promelaxin arm, respectively). In the primary analysis, the 95% confidence interval (CI) for the treatment's effect lay entirely above the non-inferiority margin in both Full Set (FAS) and Per Protocol (PP) analyses, providing evidence of the non-inferiority of Promelaxin vs. PEG 4000 [response rate difference: 16.5% (CI 1.55-31.49%) and 11.03% (CI −5.58 to 27.64%), FAS and PP analyses, respectively]. Mean compliance to the randomized treatment was >80% in both arms. Secondary endpoints did not significantly differ between the two arms, except for the average number of total days of on-demand treatment that was significantly lower in the Promelaxin arm [14.6 (12.7) vs. 9.8 (9.1), mean (SD); primary endpoint responders in PEG and Promelaxin arm, respectively; p = 0.027]. Microbiota evenness significantly increased in the PEG 4000 arm at V4 as compared to the Promelaxin arm (p < 0.05). In addition, at V5, patients treated with PEG showed a significantly decreased microbiota density as compared to patients treated with Promelaxin (p = 0.036).Conclusions: Promelaxin microenemas are non-inferior to oral PEG in children with FC.Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02751411.